Squamous cell carcinoma: variation on dermatoscopy vascular features between well and non-well differentiated tumors - John Pyne; Devendra Sapkota; Jian Cheng Wong (Mattioli1885, 2012)
Objective: Compare the dermatoscopy vascular features of well differentiated with non-well differentiated squamous cell carcinoma (SCC). Design: A prospective study of 294 consecutive cases of histopathologically confirmed invasive SCC compared the dermatoscopic vascular features of well to combined moderate and poorly differentiated tumors. These features were recorded live directly from the patients and included: the percentage of pink in the tumor, the presence of branching, serpentine, dot, hairpin, glomerular and linear vessels, and the number of these vessel types present within each tumor. Vessel types were also reviewed by tumor depth in 1 mm increments. Setting: Two medical practices in Sydney, Australia. Patients: Eighty-six female and 208 male patients (29-95 years old). Main outcome measure: Dermatoscopic vascular feature variation between grades of tumor differentiation and tumor depth. Results: Of 294 invasive SCCs, 255 (87%) were well differentiated, 32 (11%) were moderately differentiated and 7 (2%) were poorly differentiated. The percentage of pink areas within tumors varied between differentiation grades. The combined group of moderate and poorly differentiated tumors displayed more branching (28%, P<0.001) and serpentine (62%, P<0.005) blood vessels compared to well differentiated tumors (8% and 38%, respectively). Moderate and poorly differentiated tumors displayed larger numbers of vessel types (3.3) compared to well differentiated tumors (2.6, P < 0.01). Branching and serpentine vessels both increased in incidence with increasing tumor depth (p<0.05). Conclusion: Grades of tumor differentiation in SCC display varying dermatoscopic vascular features. The incidence of branching and serpentine vessels increases with increasing tumor depth and the shift towards poor differentiation.